Ethnic Enclaves, Economic and Political Threat: An Investigation With the European Social Survey - Demireva, Neli; Zwysen, Wouter (Frontiers in Sociology, 2021)
Using data from the 2002 and 2014 waves of the European Social Survey, enriched with contextual data, we examine the impact of ethnic enclaves upon their majority, minority and migrant residents. Such local areas are often presented as problematic by politicians, and there is little rigorous examination of these claims. In addition, as our data shows, ethnic enclaves often happen to be residential areas blighted by structural disadvantage such as higher unemployment or crime rates. If fears that majority members at the bottom of the wealth hierarchy experience growing economic competition with migrants and minorities are well-founded, the ethnic enclave should have a pronounced negative impact upon the economic outcomes of majority members (no support for this argument with our data). If the threat is to political primacy, the residence in the ethnic enclave should be associated with rise in the propensity of the majority to vote for the far right and be dissatisfied with democracy (we find strong support for both). There is however an economic enclave penalty associated with the labour market insertion of migrants and the job quality of the second generation, and ethnic enclaves also increase the dissatisfaction with democracy of minority members.